Iron Induces Anti-tumor Activity in Tumor-Associated Macrophages - Costa da Silva, Milene; Breckwoldt, Michael O.; Vinchi, Francesca; Correia, Margareta P.; Stojanovic, Ana; Thielmann, Carl Maximilian; Meister, Michael; Muley, Thomas; Warth, Arne; Platten, Michael; Hentze, Matthias W.; Cerwenka, Adelheid; et al. (Frontiers in Immunology, 2017)
Tumor-associated macrophages (TAMs) frequently help to sustain tumor growth and mediate immune suppression in the tumor microenvironment. Here we identified a subset of iron-loaded, pro-inflammatory TAMs localized in hemorrhagic areas of the tumor microenvironment. The occurrence of iron-loaded TAMs (iTAMs) correlated with reduced tumor size in patients with non-small cell lung cancer. Ex vivo experiments established that TAMs exposed to hemolytic red blood cells were converted into pro-inflammatory macrophages capable of directly killing tumor cells. This anti-tumor effect could also be elicited via iron oxide nanoparticles. When tested in vivo, tumors injected with such iron oxide nanoparticles led to significantly smaller tumor sizes compared to controls. These results identify hemolytic red blood cells and iron as novel players in the tumor microenvironment that repolarize TAMs to exert direct anti-tumor effector function. Thus, the delivery of iron to TAMs emerges as a simple adjuvant therapeutic strategy to promote anti-cancer immune responses.